¿Por qué decimos que «no podemos hacer intervención social»? - Molleda Fernández, Esperanza (Cuadernos de Trabajo Social, 2007)
A frequent complaint among social workers is that it is not possible for social workers to do authentic social work and that it is only possible to manage social resources. With this starting point, this article studies the need to delve deeper into areas such as the importance of theory for Social Work, the meaning of our profession in current society, the goals that are pursued through our interventions, of what it means to do social work and what are the basic tenets of our work, as well as the existence of the unavoidable ethical dilemma in which social workers find themselves when they have to make decisions that will affect the life and person of our clients. These aspects tell an account of the difficulties involved in doing social work.